BRMS1 coordinates with LSD1 and suppresses breast cancer cell metastasis - Qiu, Rongfang (Am J Cancer Res, 2018)
Breast carcinoma metastasis suppressor gene 1 (BRMS1) encodes an inhibitor of metastasis and is reported in many types of tumor metastasis. However, the mechanism of BRMS1-mediated inhibition of breast cancer metastasis at the transcriptional level remains elusive. Here, we identified using affinity purification and mass spectrometry (MS) that BRMS1 is an integral component of the LSD1/CoREST corepressor complex. Analysis of the BRMS1/LSD1 complex using high-throughput RNA deep sequencing (RNA-seq) identified a cohort of target genes such as VIM, INSIG2, KLK11, MRPL33, COL5A2, OLFML3 and SLC1A1, some of which are metastasis-related. Our results have showed that BRMS1 together with LSD1 are required for inhibition of breast cancer cell migration and invasion. Collectively, these findings demonstrate that BRMS1 executes transcriptional suppression of breast cancer metastasis by associating with the LSD1 and thus can be targeted for breast cancer therapy.